O envelhecimento nas organizações: das percepções de gestores de recursos humanos às práticas de gestão da idade - Cepellos, Vanessa Martines (2013)
This research discusses issues related to aging in organizations and aims to investigate the relationship between the Human Resources (HR) managers attitudes regarding older workers and management practices of the age. The study aims contribute to the advancement of the discussion regarding aging issue in Brazil and its implications for organizations. This subject concerns both the academic field of organizational studies, as well as professionals in public and private areas. For this a descriptive study of quantitative character was conducted. Regarding theoretical foundations, concepts were discussed related to the meanings of age, aging, ageism (ageism), attitudes concerning older professionals and practices of age management. Primary data were collected through questionnaires, totaling 138 HR managers. The results were analyzed and discussed in the light of the theoretical foundations of this study. The research allowed to conclude that, in general, these managers have a positive attitude about older professionals, although it does not reflect the adoption of age management practices, which proved slightly adopted by companies. There were identified inconsistencies in the managers answers, which enabled a reflection of the bias that causes politically correct themes about prejudice and discrimination. It was possible to infer that, in general, companies are not prepared for the scenario of an aging productive force that is projected for the next two decades in Brazil.